European rabbits as ecosystem engineers: warrens increase lizard density and diversity - Gálvez Bravo, Lucía; Belliure, Josabel; Rebollo, Salvador (Biodiversity and Conservation, 2008)
Mammals that build extensive open burrow systems are often classiﬁed as ecosystem engineers, since they have the potential to modulate the availability of resources for themselves and other organisms. Lizards may beneﬁt from the heterogeneity created by these structures, especially if coupled with an increased offer of sites for refuge and thermoregulation. However, information about these engineering effects by burrowing animals is scarce. We investigated the inﬂuence of European rabbit burrows on several parameters of a Mediterranean lizard community (abundance, density, diversity and body condition) in three different habitats (open pastures, holm oak and scrub patches). We found that lizards were positively associated with burrows, and that burrows determined lizard presence at otherwise unfavourable habitats. Moreover, community parameters such as density and species richness were higher in sites with burrows. Burrows inﬂuenced lizard species in different ways, and were also relevant for other Mediterranean vertebrates, as revealed by questionnaires to experts. We also explored the possible resources provided by burrows for lizards. Warrens offer relatively abundant prey and appropriate retreat sites for refuge and thermoregulation. Warrens may have further implications within the ecosystem, acting as stepping stones, allowing lizards to reach otherwise inaccessible habitat patches. This study shows that European rabbit warrens have a positive inﬂuence on lizard density and diversity, and conﬁrms the role of rabbits as ecosystem engineers. This reinforces the need for appropriate conservation measures for rabbits, especially given their threatened status in the Iberian Peninsula. Furthermore, our study highlights that taking into account the inﬂuence of engineering activities increases our awareness of species interactions, and may translate into more adequate conservation measures for the preservation of biodiversity.
Keywords: Burrows; Dehesa; Mediterranean; oryctolagus cuniculus; Stepping stones